Understanding the Economic Impact of Tourism – a Comparative Analyses - Nedelea, A.; Неделя, A.; Elmazi, L.; Елмазі, Л.; Totska, Olesia Leontiivna; Тоцька, Олеся Леонтіївна (My University, 2008)
In the article an authors examine economic benefits and costs, related to tourism; direct, indirect and induced effects of tourism; specify on expedience of isolation of tourism as a distinct sector in systems of national accounts. Розглянуто економічні вигоди та затрати, пов’язані з туризмом, прямі, опосередковані та вимушені ефекти туризму; вказано на доцільність виокремлення туризму як сектору в системах національних рахунків.
Розуміння економічного впливу туризму – порівняльний аналіз.
A. Nedelea – Ph. D. Stefan cel Mare University, Suceava,Romania; L. Elmazi – Ph. D. Marketing and Tourism Department,Faculty of Economics, University of Tirana, Albania; O. Totska – Senior teacher, Chair of finance of the enterprises and credit, Volyn National University named after Lesya Ukrainka, Ukraine
Keywords: benefits; вигоди; costs; затрати; tourism; туризм